2021
DOI: 10.1097/md.0000000000026978
|View full text |Cite
|
Sign up to set email alerts
|

Breast reconstruction during the COVID-19 pandemic

Abstract: Background:The novel coronavirus disease 2019 (COVID-19) has changed people's way of life and posed great challenges to plastic surgery. Most of plastic surgeries are considered elective surgeries and are recommended to be delayed. But breast reconstruction in plastic surgery is special. Doctors’ associations from different countries have different rules on whether breast reconstruction surgery should be delayed. For the controversial topic of immediate breast reconstruction in the COVID-19 pandemic, we conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Several studies performed since have shown the strict institutional restrictions placed on all autologous breast reconstructions, with 47.7% of surgeons reporting performing only alloplastic reconstructions during the pandemic, while 15.9% reported restrictions on all forms of breast reconstruction. 30 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies performed since have shown the strict institutional restrictions placed on all autologous breast reconstructions, with 47.7% of surgeons reporting performing only alloplastic reconstructions during the pandemic, while 15.9% reported restrictions on all forms of breast reconstruction. 30 , 38 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the ASPS recommended in March 2020 that autologous reconstructions are delayed and immediate alloplastic reconstruction be performed on a case‐by‐case basis, depending on resource availability, the patient's comorbidities, and the likelihood of complications. Several studies performed since have shown the strict institutional restrictions placed on all autologous breast reconstructions, with 47.7% of surgeons reporting performing only alloplastic reconstructions during the pandemic, while 15.9% reported restrictions on all forms of breast reconstruction 30,38–40 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations